What causes the death of dopaminergic neurons in Parkinson’s disease? - Surmeier, D. James; Guzman, Jaime N.; Sanchez-Padilla, Javier; Goldberg, Joshua A. (Progress in Brain Research, 2010)
The factors governing neuronal loss in Parkinson’s disease (PD) are the subject of continuing speculation and experimental study. In recent years, factors that act on most or all cell types (pan-cellular factors), particularly genetic mutations and environmental toxins, have dominated public discussions of disease aetiology. Although there is compelling evidence supporting an association between disease risk and these factors, the pattern of neuronal pathology and cell loss is difficult to explain without cell-specific factors. This chapter focuses on recent studies showing that the neurons at greatest risk in PD – substantia nigra pars compacta (SNc) dopamine (DA) neurons – have a distinctive physiological phenotype that could contribute to their vulnerability. The opening of L-type calcium channels during autonomous pacemaking results in sustained calcium entry into the cytoplasm of SNc DA neurons, resulting in elevated mitochondrial oxidant stress and susceptibility to toxins used to create animal models of PD. This cell-specific stress could increase the negative consequences of pan-cellular factors that broadly challenge either mitochondrial or proteostatic competence. The availability of well-tolerated, orally deliverable antagonists for L-type calcium channels points to a novel neuroprotective strategy that could complement current attempts to boost mitochondrial function in the early stages of the disease.